2012
DOI: 10.1155/2012/656353
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterisation of ZnO Particles Obtained by the Emulsion Precipitation Method

Abstract: Zinc oxide was obtained by precipitation in an emulsion system with zinc acetate used as a precursor of ZnO and potassium hydroxide or sodium hydroxide as a precipitating agent. The cyclohexane, as an organic phase, and a nonionic surfactant mixture were also used for preparation of the emulsion. By applying modifications of the ZnO precipitation process, such as changing the precipitating agent, composition of substrates, and the rate of substrate dosing, some interesting structures of ZnO particles were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 52 publications
8
56
0
2
Order By: Relevance
“…Unfortunately, the method used to make these measurements (film flakes inside KBr pellets) precludes any attempt of quantification. Consequently, although one can see varying intensities of the carboxylate and (aliphatic) C-H-stretching bonds [21] (inset of Fig.5b) from film to film, from these slight differences one cannot infer higher or lower organic content. Instead, the elemental C and N contents have been quantified by EOA.…”
Section: Tg/dsc Experimentsmentioning
confidence: 96%
“…Unfortunately, the method used to make these measurements (film flakes inside KBr pellets) precludes any attempt of quantification. Consequently, although one can see varying intensities of the carboxylate and (aliphatic) C-H-stretching bonds [21] (inset of Fig.5b) from film to film, from these slight differences one cannot infer higher or lower organic content. Instead, the elemental C and N contents have been quantified by EOA.…”
Section: Tg/dsc Experimentsmentioning
confidence: 96%
“…Many metal oxides and sulfides such as TiO 2 , Cu 2 O, Al 2 O 3 , Co 3 O 4 , MgO, Fe x O y , ZnS and CdS have been used to modify the CNTs [12][13][14][15]. Zink oxide is a semiconductor material with an energy gap of 3.37 eV and a large exciton binding energy (60 meV) at room temperature [16][17][18][19]. ZnO has remarkable physical and chemical properties including nontoxic nature, low cost, high optical activity and stability, high sensitivity of UV-Vis light and high thermal and mechanical stability at room temperature [12,13,16,17,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Zink oxide is a semiconductor material with an energy gap of 3.37 eV and a large exciton binding energy (60 meV) at room temperature [16][17][18][19]. ZnO has remarkable physical and chemical properties including nontoxic nature, low cost, high optical activity and stability, high sensitivity of UV-Vis light and high thermal and mechanical stability at room temperature [12,13,16,17,20,21]. These properties revealed that the ZnO is a useful material in electronics, optics, photonics, room temperature UV lasers, light emitting diodes and sensors [10-13, 20, 22].…”
Section: Introductionmentioning
confidence: 99%
“…This was due to the decomposition of carbonates groups and the remaining organic substances (surfactant). 25,30,31 From these results, the endothermic peak and weight loss was attributed to de-carboxylation and de-hydroxylation. 31 For this reason, to satisfy the formation of ZnO structure, calcination was done only at 450 C (see Fig.…”
Section: Resultsmentioning
confidence: 90%
“…26,30,31 The zinc nitrate hexahydrate solution, precipitant, and surfactants in WP1, WP2, and OP, respectively, were rapidly mixed, ltered and dried. Then the NZnO powders were formed aer annealing at 450 C. These parameters were maintained to achieve the porous structure orientation and particle size distribution of the NZnO powders (see Fig.…”
Section: Resultsmentioning
confidence: 99%